2011
DOI: 10.1002/hbm.21220
|View full text |Cite
|
Sign up to set email alerts
|

Staying responsive to the world: Modality‐specific and ‐nonspecific contributions to speeded auditory, tactile, and visual stimulus detection

Abstract: Sustained responsiveness to external stimulation is fundamental to many time-critical interactions with the outside world. We used functional magnetic resonance imaging during speeded stimulus detection to identify convergent and divergent neural correlates of maintaining the readiness to respond to auditory, tactile, and visual stimuli. In addition, using a multimodal condition, we investigated the effect of making stimulus modality unpredictable. Relative to sensorimotor control tasks, all three unimodal det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 169 publications
6
44
0
Order By: Relevance
“…Our observation of sustained brainstem activation for cued task blocks is in line with previous studies on intrinsic alertness and vigilance that consistently have found brainstem activation associated with maintaining responsiveness in cognitive tasks (Langner et al, 2012;Paus et al, 1997;Périn et al, 2010;Sturm et al, 1999). It has been suggested that midbrain and brainstem structures are involved in arousal systems important for maintaining optimal efficiency of information processing.…”
Section: Discussionsupporting
confidence: 91%
“…Our observation of sustained brainstem activation for cued task blocks is in line with previous studies on intrinsic alertness and vigilance that consistently have found brainstem activation associated with maintaining responsiveness in cognitive tasks (Langner et al, 2012;Paus et al, 1997;Périn et al, 2010;Sturm et al, 1999). It has been suggested that midbrain and brainstem structures are involved in arousal systems important for maintaining optimal efficiency of information processing.…”
Section: Discussionsupporting
confidence: 91%
“…A high probability for co-activation of the bilateral aINS with the MCC/SMA is a well replicated finding (for example Lie et al 2006;Hoffstaedter et al 2013;Chechko et al 2012;Veldhuizen et al 2011;Jackson et al 2005;Langner et al 2012). Thus, bilateral aINS and the MCC/SMA are thought to form a core "salience network," relevant for entering and maintaining a cognitive set (Dosenbach et al 2006) and initiating cognitive control signals (Menon and Uddin 2010) in order to regulate activity in other systems/networks (Sridharan et al 2008).…”
Section: Functional Connectivity and Cognitive Flexibilitymentioning
confidence: 85%
“…As long as the predictions stored in the loop are successfully aligned to external inputs there is no need to interrupt and update the internal model, albeit this possibility is given in the model by strong signals from V5. According to these considerations, the cerebellum would be of great importance to support the detection of prediction errors and thereby supporting predictive coding (Rao and Ballard, 1999;Langner et al, 2012;Schlerf et al, 2012). On a perceptual level, crus I has previously been associated with the cancellation of eye-movement-induced retinal image motion (Lindner et al, 2006), which might support the possible role of the cerebellum in predictive coding during visual processing.…”
Section: State Estimations Of the Cerebellum During Visual Attentionmentioning
confidence: 95%